PENERAPAN METODE PEMBELAJARAN VISUALIZATION AUDITORY KINESTETIC (VAK) PADA PEMBELAJARAN IPA UNTUK MENGAKOMODASI KESIAPAN DAN GAYA BELAJAR SISWA KELAS V - Rustianingsih, Rika; Nisa, Ana Fitrotun (Universitas Sarjanawiyata Tamansiswa, 2020)
This research aims to know the implementation of the Visualization Auditory Kinesthetic (VAK) learning method in learning science to accommodate the readiness and learning style based on the improvement of fifth grades students’ learning outcomes in Demakijo 2 Sleman Public Elementary School. The type of this research is classroom action research. Also, the research subject is fifth grades students in Demakijo 2 Sleman Public Elementary School 2019/2020 with a total of 24 students which is consisting of 17 male students and 7 female students. The object of this research is the readiness and learning style. The technique of data collection is through tests, questionnaires, observation, and documentation. The instrument in this research is the test, questionnaire, and observation sheet. The test validation uses the product-moment correlation formula and the reliability test uses the descriptive analysis technique. The result of this research represents that there is a student improvement in learning outcomes. In the pre-action, the class average is under the minimum criteria of mastery (KKM), which is 70.17 with the classical 41.67%. In the first cycle, the class average improves to be 76.58 with the classical 58.33%. In the second cycle, the average value improves to be 89 with the classical 83.33%. Based on the explanation, it can be concluded that the implementation of the VAK learning method can accommodate the readiness and learning style of students based on the students’ learning outcomes.